TEACHERS’ WAYS IN MAXIMIZING STUDENT TALKING TIME (STT) IN EFL CLASSROOM - DESI WIJAYANTI MA’RUFAH (Tarling : Journal of Language Education, 2018)
A Descriptive Study was conducted at the ten grade of SMAN 1 Purbalingga, revealed the teachers’ ways in maximizing STT in the EFL class. The data, which were collected and analyzed from observation, interview, and questionnaire, showed that the classroom management is important to make a good atmosphere in teaching learning process. Making an interactive classroom by reducing the central (and traditional) position and by giving chances for students to express themselves in meaningful ways are very effective to create the opportunities in STT. Also, using pair and group work which have various activities are able to build the students’ enthusiasm in their talking and give much time to talk. Moreover, by giving questions such as knowledge and comprehension questions is able to stimulate students to speak and give the time to practice their languages. The most effective way in maximizing STT is by giving chances for students to express themselves in meaningful ways and the least effective way is giving questions.